Representasi Kekerasan terhadap Perempuan pada Film 27 Steps of May - Lulut Lusianukita; Sunarto . (Interaksi Online, 2020)
Violence against women continues to increase every year, Komnas Perempuan hopes for the ratification of the RUU PKS (Constitutional’s Draft of Eliminating Sexual Violence) to protect victims. But in reality RUU PKS continues to be pros and cons, one of the ways that can be done to voicing minorities is through mass media such as films. Influenced by patriarchal social conditions, it needs to be seen how Indonesian films presenting the theme of violence against women, it is necessary to see how Indonesian films present the theme of violence against women, whether it is told from the point of view of women or men. The study entitled "Representation of Violence Against Women in " 27 Steps of May "aims to describe the depiction of violence against women in the film 27 Steps of May and see the dominant ideology in the text. The theory used in this research is Standpoint Theory to see whether there is women's resistance shown in scenes of sexual violence. This research is descriptive study using a qualitative approach with John Fiske's semiotic analysis method through 3 levels of analysis, the level of reality, the level of representation and the level of ideology. The results of this research at the reality level showing stereotypes of women so that they can become objects of sexual violence. At the representation level, it shows that rape scenes were made using a male perspective and objectifying women's bodies.At the ideological level, patriarchal ideology is seen with the assumption that women can be owned by men and are part of men, there is also gender ideologies that shape social values by generating discrimination primarily on women. The researcher suggests to provide variations on similar research to see audience acceptance on the issue of violence, then the community can reflect on it to see gender construction. Through this study, researchers also saw the need for film workers to explore the roles of women not only under male domination.